Patients, doctors and experimentation: doubts about the Declaration of Helsinki. - Belsey, A (1978)
The World Medical Association's Declaration of Helsinki offers guidelines to doctors engaged in biomedical research with human subjects. The fundamental distinction of the Declaration is between clinical research combined with professional care and non-clinical scientific research. If hospital patients are the experimental subjects, then the former research must be carried out by the patient's own doctor, whereas the latter research must not be; it must be carried out by other doctors. The relevance of the distinction between the patient's own doctor and other doctors is challenged and an alternative conception of the patient-doctor relationship is drawn, together with an alternative justification, based on the work of Hans Jonas, of the use of patients in research. Finally, the political nature of the patient-doctor relationship is mentioned, and it is claimed that the alternative conception of this relationship developed in the paper is more in line with the ethical principles of the Hippocratic tradition.